Impact of different assumptions on estimates of childhood diseases obtained from health care data: A retrospective cohort study. Issue 6 (24th April 2018) - Osokogu, Osemeke U.; Pacurariu, Alexandra; Mosseveld, Mees; Rijnbeek, Peter; Weibel, Daniel; Verhamme, Katia; Sturkenboom, Miriam C.J.M.
Abstract: Purpose: Accurate estimates of disease incidence in children are required to support pediatric drug development. Analysis of electronic health care records (EHR) may yield such estimates but pediatric‐specific methods are lacking. We aimed to understand the impact of assumptions regarding duration of disease episode and length of run‐in period on incidence estimates from EHRs. Methods: Children aged 0 to 17 years (5–17 years for asthma) registered in the Integrated Primary Care Information database between 2002 and 2014 were studied. We tested the impact of the following: maximum duration of disease episode (0, 14, 30, 60, and 90 days) on recurrent diseases (acute otitis media [common] and acute pyelonephritis [rare]); and database run‐in period on chronic diseases—asthma (common) and type 1 diabetes (DM) (rare). We calculated incidence rate ratios with 95% confidence intervals and stratified using 1‐year age categories. Results: Altogether, 503 495 children were registered. The incidence of acute otitis media was highest in <2‐year‐old children; using 30 days disease duration as reference, the rate increased with 8% if the duration was 14 days and decreased with 8% when extended to 60 days. Disease duration did not impact acute pyelonephritis (rare). No run‐in (to exclude prevalent cases) versus 24‐month run‐in period overestimated the incidence rate for asthma and DM by a factor of 2. Conclusions: Analysis of EHR allows for estimation of disease incidence in children, but assumptions regarding episode length and run‐in period impact the incidence estimates. Such assumptions may be routinely explored.